Developper chez les professeurs une competence strategique de re-lecture de programmes :l'ErE et la science dans le cas de la Belgique francophone - Emmanuel Legrand (Éditions en environnement VertigO, 2003)
By the "following" of different teachers, animators and formatters and also by interviews of different actors of the scholar system, some legal components influencing the Education Environmental (EE) practice of science teachers have been pointed out (in a profound way but no exhaustive one). These contextual elements have allowed to develop, in answer, a by the author called "programme re-lecture's competence" enabling teacher to manage EE activities in the scholar system. After a presentation of the particular context (useful to the comprehension of the so called "competence"), the "programme re-lecture's competence" is decorticated and fully exemplified.